Peran Satuan Polisi Pamong Praja dalam Mendisiplinkan Reklame di Kabupaten Semarang - Ekaningsih, Lailasari; Eva Dhamalia, Dian (Universitas Ekasakti, 2024)
The Civil Service Police Unit, abbreviated as Satpol PP, is an instrument of the Regional Government in maintaining peace and public order and enforcing Regional Regulations. In this article, the role of the Semarang Regency Satpol PP is to have the authority to control and supervise advertising violations related to permits and installation procedures, whether carried out in a persuasive or repressive pattern. The efforts made in the disciplinary operation for holding advertisements carried out by the Semarang Regency Satpol PP had several obstacles. These obstacles are the size of the area, the lack of Satpol PP personnel and the lack of mobilization facilities used. So the Satpol PP has a solution, namely coordinating with BKUD regarding Semarang Regency PP permits and taxes by collaborating with the Semarang Regency Regional Financial Agency (BKUD). Apart from that, maximizing the online complaint facilities that have been provided, namely the Quick Response System